The use of apolipoprotein A-I as a transport form of the green fluorescent protein GFP gene in rat hepatocytes - L. M. Polyakov; D. V. Sumenkova; M. V. Kotova; N. V. Trifonova; R. A. Knyazev (Сибирский научный медицинский журнал)
The aim of this study was to investigate the possibility of using apolipoprotein A-I (apo A-I) as a transport form of the green fluorescent protein (GFP) gene into rat hepatocytes.Material and methods. A culture of isolated rat hepatocytes was used as a model. Apo A-I conjugate with fluorescein isothiocyanate (FITC) was obtained by incubation of apo A-I protein with FITC in carbonate buffer pH 9.5 at a ratio of 12.5 μg FITC per 1 mg of protein. Plasmids for pE-GAG transfection with an integrated GFP gene were enriched in the promoter part with cis-elements of the CC(GCC)3-5 type to enhance complex formation with apo A-I. An inverted fluorescence microscope was used for visual analysis of cell fluorescence.Results and discussion. The paper presents evidence of FITC-labeled apo A-I penetration into the cytoplasm and nuclei of rat hepatocytes by receptor-mediated endocytosis. On this basis, it is proposed an attempt to use apo A-I as a means of targeted delivery of plasmid DNA with an integrated GFP gene into the cell. According to the results of fluorescence microscopy, the use of apo A-I as a plasmid DNA transfection agent led to the accumulation of the GFP protein in the cytoplasm of hepatocytes. No fluorescent protein was observed in the absence of apo A-I.Conclusions. The result obtained may indicate the delivery of the GFP gene to the nuclear apparatus of the cell, its expression and GFP protein synthesis.